2016
DOI: 10.31248/rjfsn2016.010
|View full text |Cite
|
Sign up to set email alerts
|

Thin layer modelling of hybrid, solar and open sun drying of tomato slices

Abstract: The thin layer drying behaviour of tomato slices dried using hybrid drying method as well as solar and open sun drying was investigated. Six thin layer drying models (Page, Logarithmic, Henderson and Pabis, Newton (Lewis), Wang and Singh and Parabolic) were used to optimize the goodness of fit to the experimental data. The models were compared using coefficient of determination (R 2), chi-square ( 2) and root mean square error (RMSE). The tomato slice dried faster when subjected to hybrid drying method compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 29 publications
6
24
0
Order By: Relevance
“…Faster drying rates were observed at 2 mm and 4 mm thicknesses compared to the 6 mm and 8 mm thicknesses for drying of the African star apple. This result corroborated with Hussein, et al [12] findings in which the drying time reduced significantly as the thickness of slices decreases, because the resistance to moisture movement is relatively higher in thicker slices than in thinner ones. Also, the rate of drying at 60 ºC was faster as shown in Figure 3.…”
Section: Drying Characteristicssupporting
confidence: 90%
See 1 more Smart Citation
“…Faster drying rates were observed at 2 mm and 4 mm thicknesses compared to the 6 mm and 8 mm thicknesses for drying of the African star apple. This result corroborated with Hussein, et al [12] findings in which the drying time reduced significantly as the thickness of slices decreases, because the resistance to moisture movement is relatively higher in thicker slices than in thinner ones. Also, the rate of drying at 60 ºC was faster as shown in Figure 3.…”
Section: Drying Characteristicssupporting
confidence: 90%
“…This was due to high temperature gradients created by higher temperature which ease the migration of water from the inner part to the surface to get evaporated. The ease of this migration depends on the porosity of the samples, drying temperatures and the surface area available as reported by Hussein, et al [12]. The study also confirmed the reports of Tunde-Akintunde and Oke [13] and Sobukola [14] on plantain and apple thin layer drying, respectively.…”
Section: Drying Characteristicssupporting
confidence: 89%
“…However, Hussein et al. (2016) reported that this traditional open sun drying took a longer drying time that gave adverse changes to the qualities of the end products. Enzymatic and microbial activity or contamination with dust and insects may also affect the final products.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the coefficient of determination, the goodness of fit was determined by various statistical parameters such as reduced mean square of the deviation χ² and root mean square error (RMSE). For quality fit, R² value should be higher, close to one, and χ² and RSME values should be lower [34,39].…”
Section: Mathematical Modellingmentioning
confidence: 99%
“…These simple models, also known as thin layer models, allow prediction of mass transfer during dehydration and are applied to simulate drying curves under similar conditions [22,23]. Many researches have been conducted on the mathematical modeling and experimental studies on thin layer drying processes of various vegetables and fruits, such as green bean [24,25] red pepper [26], mint leaves [27], tarragon [28], potato [29], chilli pepper [30], carrot [31], citrus aurantium leaves [32], tomato slice [33][34][35] and Onion slice [16]. However, few reports have focused on the evaluation of a suitable drying model for describing the drying kinetic of osmotically pretreated red onion varieties.…”
Section: Mathematical Modellingmentioning
confidence: 99%